Exotic vegetable offerings in Roman Sacrifice - Alvar Nuño, Antón (ARYS. Antigüedad: Religiones y Sociedades, 2020)
Although vegetable offerings are generally admitted in the main definitions of sacrifice, they are not included in the analysis of this kind of ritual practice: the violent act of animal sacrifice is frequently over-emphasized while vegetables are neglected. However, vegetable offerings are also sensitive to the dynamics of religion; the study of the ways they are used in the ritual of sacrifice allows us to appreciate its ambiguities and constant reelaborations. I analize in this paper the use of exotic spices and vegetables in roman sacrifice stressing their importance in the processes of continuity and change, their symbolic value and their inclusion in theological reflections by roman literates.
Keywords: Sacrifice; continuity and change; symbolic value; exotic spices; exotic vegetables; literary representations